2015
DOI: 10.1021/ja511619c
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic Transformation of Aliphatic Alcohols to Corresponding Esters in O2 under Neutral Conditions Using Visible-Light Irradiation

Abstract: Selective oxidation of aliphatic alcohols under mild and base-free conditions is a challenging process for organic synthesis. Herein, we report a one-pot process for the direct oxidative esterification of aliphatic alcohols that is significantly enhanced by visible-light irradiation at ambient temperatures. The new methodology uses heterogenerous photocatalysts of gold-palladium alloy nanoparticles on a phosphate-modified hydrotalcite support and molecular oxygen as a benign oxidant. The alloy photocatalysts c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
87
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 123 publications
(91 citation statements)
references
References 49 publications
3
87
1
Order By: Relevance
“…Co-deposition-reduction can also be performed. Au-Pd nanoparticles were prepared on phosphate-modified hydrotalcite by co-impregnation with a solution of HAuCl 4 and PdCl 2 followed by chemical reduction obtained by addition of lysine (pH 8-9) then of NaBH 4 , washed and dried at 60˝C [46]. Nanoparticles of 4-5 nm with a d-spacing attesting the formation of Au-Pd alloy were obtained.…”
Section: Photo-depositionmentioning
confidence: 99%
“…Co-deposition-reduction can also be performed. Au-Pd nanoparticles were prepared on phosphate-modified hydrotalcite by co-impregnation with a solution of HAuCl 4 and PdCl 2 followed by chemical reduction obtained by addition of lysine (pH 8-9) then of NaBH 4 , washed and dried at 60˝C [46]. Nanoparticles of 4-5 nm with a d-spacing attesting the formation of Au-Pd alloy were obtained.…”
Section: Photo-depositionmentioning
confidence: 99%
“…Also, heterogeneous Pd catalysts can be easily recovered from the reaction mixture and reused for several reaction cycles. Recently, by using plasmonic nanoparticles, the rates of Pd-catalyzed reactions such as crosscoupling, 16,17 hydrogenation, [18][19][20][21] and oxidation reactions [22][23][24] have been improved, and it has been found that bimetallic nanoparticles show superior activity compared to the pure metallic nanoparticles. 25,26 The most studied bimetallic catalysts in plasmon-enhanced Pd-catalyzed reactions are AuPd bimetallic nanoparticles.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, noble metal has plasmonic effect and induces the organic reaction under visible light and enhances the conversion efficiency [140]. Combining with semiconductor nanocrystals, metal/semiconductor hybrid nanocrystals have potential advantages in organic photosynthesis: higher conversion efficiency, higher selectivity, and lower by-products [141][142][143].…”
Section: Some Other Recent Photosynthesis Applications Of Metal/semicmentioning
confidence: 99%
“…Beside, metal/semiconductor hybrid nanocrystals, such as Au/ZrO 2 , can be used for other organic reaction: reduction of nitroaromatic compound, Suzuki reaction, ester reaction. and so on [140,[142][143]. In summary, metal/semiconductor photocatalysts have shown their potential application on hydrogen evolution, photoreduction for conversing CO 2 into fuel and organic photosynthesis.…”
Section: Some Other Recent Photosynthesis Applications Of Metal/semicmentioning
confidence: 99%